Cardiometabolic Complications after Androgen Deprivation Therapy in a Man with Prostate Cancer: Effects of 3 Years Intermittent Testosterone Supplementation - Aversa, Antonio; Francomano, Davide; Lenzi, Andrea (Frontiers in Endocrinology, 2012)
Androgen deprivation therapy (ADT) for prostate carcinoma (PCa) may cause cardiometabolic complications unless intermittent androgen blockade (IAB) is instituted. An 80-year-old man was diagnosed intermediate grade (Gleason 4+3) PCa and was treated with continuous ADT with triptorelin plus bicalutamide. After 6 months of treatment, he experienced an acute myocardial infarction and one month after hospitalization he came to our outpatient clinic for fatigue, weight gain and hyperglycemia. Due to iatrogenic hypogonadism, we decided to proceed with IAB, but after three months ADT withdrawal his serum testosterone (T) was still 0.5 ng/mL. Due to very low concomitant PSA levels (0.1 ng/mL) he was then proposed intermittent T-gel supplementation (Tostrex®) which was initiated according to the following scheme: 6 months on and three months off. T-gel dose was titrated tri-weekly in order to achieve T plasma levels below 3.49 ng/mL. After six months on, his serum T raised to a mean value of 2.0 ng/mL without increments in PSA. After overall twelve months on, his serum T peaked to a mean value of 3.0 ng/mL while a delay in PSA rise was seen after 24 mo (0.6 ng/mL) but remained stable until the last observation carried forward (LOCF), at 45 months. No clinical and biochemical PCa progression were observed at LOCF. Reversion of iatrogenic metabolic syndrome started after six mo of T supplementation without using any add-on treatment. This case provides support that once regression of PCa growth is attained, T supplementation may be administered in well differentiated PCa, especially if IAB is not successful in reverting iatrogenic hypogonadism and its associated cardiac and metabolic complications.